The acceptance towards assisted reproductive technologies (art) among ruminant farmers in Kelantan - Mohamad Shaheen Sharun (2018)
In this current time, the population of malaysians are continuing to increase year by year. This has result to the increase of meat consumption in malaysia. Despite poultry and pork production has reached self-sufficiency, beef subsector has failed to do so. Thus, this study was conducted to determine the acceptance of assisted reproductive technologies among ruminant farmers in kelantan. There are three different independent variables that will be measured, namely, perceived usefulness, perceived ease of use and attitude. A total of 87 respondents among ruminant farmers in kelantan have been selected in this study through simple random sampling technique. Based on the findings, highest level was contributed by attitude, followed by perceived usefulness and perceived ease of use. Besides that, perceived usefulness was found to have the highest strength of relationship with the acceptance of assisted reproductive technologies, followed by attitude and perceived ease of use. Hence, this study can be concluded that perceived usefulness is the main driving factor towards the acceptance of assisted reproductive technologies among ruminant farmers in kelantan followed by attitude and perceived ease of use.